Assessment of establishment and operations under market conditions for a public equity fund - Jaka Vadnjal (Central European Public Administration Review)
The government of Slovenia established a publicly funded venture capital fund in order to provide start-up finance for small companies. The fund was meant to fill in the market gap in early-stage equity finance supply. The fund is co-financed from EU structural funds and has to comply with strict regulation regarding possibility of market distortion from such measure. The objective of the study is to give a straightforward answer whether the public fund will behave within the equity market conditions or will impose an unloyal competition to the existing privately financed funds. In accordance to this, an evaluation is given advising that the public fund should not be regarded as a state-aid measure.